2021
DOI: 10.5902/1980509816116
|View full text |Cite
|
Sign up to set email alerts
|

Análise e distribuição espacial do ruído no posto de trabalho do operador e nas proximidades de máquinas agrícolas e florestais

Abstract: Um dos principais riscos ergonômicos ao qual são submetidos os operadores de máquinas agrícolas e florestais é o ruído. Porém, a intensidade de ruído experimentada por profissionais que atuam, tanto como operadores como auxiliares nas imediações dessas máquinas, é pouco conhecida. Por isso, esta pesquisa objetivou quantificar os níveis de ruídos sofridos por trabalhadores nas proximidades das frentes de trabalho agrícola e florestal. Para isso, foram utilizadas neste trabalho as seguintes máquinas: Trator da m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 4 publications
(4 reference statements)
1
4
0
Order By: Relevance
“…The lowest observed averages were developed at 800rpm, with differentiation in relation to the other engine speeds. The results of the present research are in agreement with those obtained by Veiga et al (2021), where the tractor cabin was able to attenuate the external noise, coming from the operation of the engine and other external components.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…The lowest observed averages were developed at 800rpm, with differentiation in relation to the other engine speeds. The results of the present research are in agreement with those obtained by Veiga et al (2021), where the tractor cabin was able to attenuate the external noise, coming from the operation of the engine and other external components.…”
Section: Resultssupporting
confidence: 92%
“…The same happened with the noise differences obtained for 2180 rpm and 2500 rpm in the engine (Figure 2). Veiga et al (2021) found noise levels above those allowed in the NR15 standard around tractors of different brands, and the safe distance to stay close to these machines varied between 3.5 and 6 meters. In the rotation of 800rpm, the noise did not exceed 85dB(A), in any of the evaluated points, indicating that the tractor at idle, without acceleration, does not offer work risk according to the regulations of the Ministry of Labor and Employment.…”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…Moreover, points with higher noise levels are concentrated in the lower part of the map, that is, in the projection of the used equipment engine. Veiga et al (2021) found a similar situation when analyzing noise distribution near agricultural and forestry machines. Likewise, Gonçalves et al (2019) evaluated noise emitted by a cutting tractor through geostatistics, finding values of 7 m in front, 7 m on the right side, 5 m on the left side, and 3 m at the rear of the evaluated equipment.…”
Section: Resultsmentioning
confidence: 53%
“…The latest discoveries in chainsaw noise state that the average noise dose exceeds the maximum allowable limit of 85 dB(A) for 8 h of continuous work [31,32]. Veiga et al [33] concluded that for the chainsaw, the maximum exposure time is one hour (without PPE). The exposure of harvester and forwarder operators to noise in karst areas does not exceed the limit for daily noise exposure defined in the EU legislation [34] but is higher than exposure in fully mechanized CTL harvesting on flat terrain [23].…”
Section: Noise and Vibrationmentioning
confidence: 99%